Multigene assays for classification, prognosis, and prediction in breast cancer: a critical review on the background and clinical utility = Multigenassays zur Beurteilung der Klassifikation, Prognose und Prädiktion beim Mammakarzinom : ein kritischer Review zum Hintergrund und klinischen Nutzen - Sinn, Peter; Aulmann, Sebastian; Wirtz, R.; Schott, Sarah; Marmé, Frederik; Varga, Z.; Lebeau, A.; Kreipe, H.; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2013)
Gene signatures which are based on multigene profiling assays have been developed for the purpose to better define the prognosis and prediction of therapy results in early-stage breast cancer. These assays were designed to be more specific than conventional clinico-pathologic parameters in the selection of patients for (neo-)adjuvant treatment and in effect help to avoid unnecessary cytotoxic treatment. In this review we describe molecular risk scores, for which tests are commercially available (PAM50®, MammaTyper®, MammaPrint®, Oncotype DX®, Endopredict®, Genomic Grade Index®) and IHC risk scores (Mammostrat® and IHC4), and discuss the current evidence of their clinical use.
Publikationsdatum: 11. Oktober 2013 (online)
Gesehen am 03.02.2022